Variability for yield and resistance to yellow vein mosaic virus disease in okra : Abelmoschus esculentus L. Moench - Kishor D S (Department of Plant Breeding and Genetics, College of Agriculture, 2012)
The present investigation on “Variability for yield and resistance to yellow vein mosaic virus disease in okra (Abelmoschus esculentus (L.) Moench)” was conducted at the Department of Plant Breeding and Genetics and Department of Plant Pathology, College of Agriculture, Vellayani during 2011-2012 and evaluation of germplasm for genetic variability, character association and resistance to yellow vein mosaic disease, confirmation of disease resistance in selected genotypes through vector and graft transmission studies, development and evaluation of F1’s for combining ability, heterosis and disease resistance were done. The okra germplasm consisting of thirty six accessions collected from different parts of Kerala and Karnataka was assessed for the extent of variability, heritability and genetic advance, the relationship among the yield and associated traits and disease scoring. Analysis of variance showed significant difference among the thirty six genotypes for all the characters studied. The germplasm possessed sufficient variability and offered scope for selection based on characters like plant height, number of primary branches, leaf axil bearing first fruit, duration, number of fruits per plant, fruit weight, fruit length and yield per plant. Five genotypes viz., AE-2 (IC 1012-1), AE-8 (Thirumala local), AE-28 (Halu Bhendi ), AE-32 (Kunnapuzha local)and AE-33 (Holavanalli local) exhibited resistance to YVMV during all the crop stages after scoring studies and resistance was confirmed to these selected ones by artificial transmission methods such as vector transmission and graft transmission in glass house. High genotypic and phenotypic coefficient of variation was noticed for almost all characters and narrow difference between GCV and PCV suggest that environmental influence is minimal for the traits studied. High estimates of heritability coupled with high to moderate genetic advance as percent over mean was recorded for all the characters considered. Yield had positive and significant association with number of fruits per plant, fruit weight, fruit girth and number of primary branches indicating that selection based on these characters may improve yield. In the line x tester analysis, the mean sum of squares due to genotypes was significant for all the characters studied. Combining ability analysis revealed higher magnitude of SCA variance for all the characters except days to first flowering and fruit girth indicating preponderance of non additive gene action. Among the hybrids cross combination Holavanalli local x Mallapalli local had high per se and sca effects for yield per plant, fruit length, fruit weight, number of fruits per plant, duration, plant height, number of primary branches, leaf axil bearing first fruit and days to first flowering and was considered as the superior hybrid followed by the cross combination Thirumala local x Punjab Phalgani which had high sca effects and standard heterosis for yield and yield contributing characters. These hybrids were also resistant to yellow vein mosaic virus disease. Based on per se performance for yield and disease resistance scores the hybrids Thirumala local x Kattakada local and Kunnapuzha local x Punjab Phalgani can also be considered as good hybrids. The cross combination Holavanalli local x Mallapalli local showed significant standard heterosis for all the characters and hence recommended for heterosis breeding.